Plant density and varietal effects on diaporthe/phomopsis diseases infection of soybean and its impact on seed quality - Raeisi Parsaei, Samiyeh (2011)
Soybean is one of the most important oilseed crops with high protein for human and animal consumptions. Environmental factors, field management and varieties affect on the quality of harvested seed. Storage environment and its duration are also known to influence pathogen survival in stored seed. A comprehensive study was undertaken at University Putra Malaysia to evaluate the effect of plant density and seasonal variations in relation to Diaporthe / Phomopsis complex (DPC) on seed yield components and quality. Three soybean varieties namely AGS190, Deing and Pershing at 300,000 and 600,000 plants per hectare were grown in the field for two seasons in 2009. Seed germination and vigour were determined using standard germination (SG), tetrazolium (TZ) and electrical conductivity (EC) tests. Seed yield components were determined at harvest maturity growth stages (R8). Culture plate method and Scanning Electron Microscopy (SEM) were used to evaluate the incidence of Phomopsis seed decay (PSD) and the progression and colonization of DPC in different parts of soybean plant from R3 until R8 plant growth stages. Ten soybean seed lots which were stored at 0°C up to 13 years were used to evaluate the presence of DPC and to identify the isolates. Morphological and molecular methods were used to determine the longevity and frequency of DPC isolates on stored and freshly harvested soybean seeds. Analysis of data showed significant differences for higher seed yield, 100 seed weight and seed viability in two seasons and they were higher in first planting season. Planting density affected on pod number per plant, height of plant, PSD infection and seed viability and vigour significantly. Higher pod number was recorded at lower plant density which was 30 pods per plant. The first node height increased at higher plant density. PSD infection was more at higher plant density, so seed viability and vigour were higher at lower plant density. The infection of PSD was 35% at higher plant density, whereas it was 27.5% at lower plant density. The varieties showed significant differences for all parameters. AGS190 with the highest 100 seed weight could produce 1839 kg seed yield per hectare. This variety also had the highest percentage of infection to DPC (41%), so it showed the lowest seed viability and vigour. The highest pod number was recorded for Deing variety, but it produced the lowest seed yield due to very small size seed. PSD infection was negatively correlated with standard germination and tetrazolium test and showed a positive correlation with electrical conductivity. Scanning electron microscopy micrograph revealed that fungi colonization and progression started at different growth stage in different parts of plant. The infection started from R4 growth stage as fungi hypha whereas alpha conidia of fungi were observed at R8 growth stage on the stem. Hypha was observed in the pod at growth stage R5 and mycelium invaded inside the pod through the stomata at growth stage R6, but alpha conidia invaded through the stomata at R7 growth stage. The seed was the last part that was infected. The mycelium penetrated inside the seed through the hilum and cracks on the surface of seed. Based on SEM observations, DPC infection can be predicted sooner than R6 growth stage, so controlling DPC presence and infection between R4-R5 can control the disease before damage being inflicted on the seed. Seven isolates of DPC were detected, identified and characterized based on morphological and molecular methods in soybean seeds for the first time in Malaysia. The isolates which were identified molecularly were chosen from seeds that showed >10% infection based on culture plate method. Most of the isolates identified, belonged to Phomopsis longicolla, and all of them were registered in National Center for Biotechnology Information (NCBI). The longevity of isolates in storage was found to be <9 years which suggested that Diaporthe /Phomosis sp. can survive up to 9 years in cold storage( 0°C). The results of this study showed that high quality soybean seed can be produced in wet and warm tropical environments like Malaysia, but it should be planted at a proper time in a production year and harvested on time, with no delay. Continuous rainfall during late plant growth stage can cause more infection of PSD which can severely affect seed quality and decrease the germinability of harvested seeds. Overall, 300,000 plant ha-1 is an acceptable planting density with proper plant managements to produce high quality soybean seeds in Malaysia.